Introduction: Complex Systems and Six Challenges for the Development of Law and the Semantic Web - Casanovas, Pompeu; Pagallo, Ugo; Sartor, Giovanni; Ajani, Gianmaria (AI Approaches to the Complexity of Legal Systems. Complex Systems, the Semantic Web, Ontologies, Argumentation, and Dialogue, 2010)
AICOL workshops aim to bridge the multiple ways of understanding legal systems and legal reasoning in the field of AI and Law. Moreover, they pay special attention to the complexity of both legal systems and legal studies, on one hand, and the expanding power of the internet and engineering applications, on the other. Along with a fruitful interaction and exchange of methodologies and knowledge between some of the most relevant contributions to AI work on contemporary legal systems, the goal is to integrate such a discussion with legal theory, political philosophy, and empirical legal approaches. More particularly, we focus on four subjects, namely, (i) language and complex systems in law; (ii) ontologies and the representation of legal knowledge; (iii) argumentation and logics; (iv) dialogue and legal multimedia.